Implementasi Pelayanan Pencatatan Akta Perkawinan Pada Dinas Kependudukan Dan Pencatatan Sipil Kota Pematangsiantar - Naomi Margretha Simanjuntak; Siti Hazzah Nur R (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
The research method used is a descriptive method with a qualitative approach. Data collection techniques were carried out by means of interviews, observations, documentation and literature studies related to the recording of marriage certificates. The data obtained were then analyzed by means of data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, data triangulation was carried out. The results of this study can be seen that the implementation of the marriage certificate registration program at the Population and Civil Registration Office of Pematangsiantar City can be said to be running quite well. This can be seen from the number of marriage certificate ownership, which is around 56.6% of the total population who are required to have a marriage certificate. It cannot be ascertained the truth of the communication with the urban villages in Pematangsiantar city. Among the people who do not know the importance of recording marriage certificates, there are also people who know the importance of recording marriage certificates